SOCIAL DIVERSITY: A LOOK AT TOURISM - GIUSTI, Antonio; VIVIANI, Alessandro (Journal of Environmental Management and Tourism, 2016)
This paper addresses the issue of social diversity, with reference to the phenomenon of tourism in Italy. Social inequality influences numerous socio-economic phenomena: tourism has been scarcely examined under this perspective. Tourism has significant effects at social level: both on travelers and on the inhabitants of the visited regions. Italy that is one of the most important touristic nations is significantly affected by the phenomena we are studying and, therefore, is an ideal context to analyze and identify the characteristics of tourism and its interaction on various aspects of social diversity. We could consider the interactions on tourism by persons with different economic and social conditions, race, gender, age, religion, mentality. These issues are usually considered by qualitative approaches. This paper attempts to give a quantitative dimension to these phenomena looking for possible statistical and administrative sources. We examined some, direct and indirect, official sources of the National Statistical System and other sources disseminated by European projects and research institutions. To get a more detailed picture of a particular form of social tourism, we used the data provided to us by a very active association in this area. This study is only a first approach in order to find a strategy to help assessing some quantitative characteristics of accessible tourism. The development of this type of tourism shall imply actions, techniques, and policies aimed at reducing the problems about social diversity in the sector, in order to make tourism become a factor of social inclusion.
Keywords: social distress; statistical sources; tourism